Palladium‐Catalyzed Cross‐Coupling of Aryl Thioacetates and Chloro(hetero)arenes. Issue 2 (24th January 2020) - Zhao, Tan; Liang, Feng; Cai, Mingjun; Chen, Junling; Kang, Chuanqing; Wang, Hongda; Wu, Qiang
Abstract: A simple and effective method for palladium‐catalyzed carbon‐sulfur bond formation was established with aryl thioacetates and chloro(hetero)arenes as starting materials. A wide range of thioacetates and chloro(hetero)arenes can be employed for the preparation of aryl sulfides in good to excellent yield. Abstract : C−S bonds : A simple and effective palladium catalyzed C–S bond formation with thioacetates and chloro(hetero)arenes has been developed. A broad variety of substrates were well converted to respective aryl sulfides in good to excellent yield.